Penerapan Pendekatan Word and Paradigm pada Proses Morfofonemik Verba Bahasa Turki - Septiarini Makodamayanti; Agus Subiyanto (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
The Turkish language is one of the languages which people nowadays learn. The Turkish language belongs to agglutinative language with a slight border between words and their morpheme, yet it has a clear border amongst the morphemes. There is a vowel harmony in the Turkish language where the sound of the last vowel of the stem affects the vowel’s sound of the attached suffixes. The existence of the vowel harmony triggers the change of the sound of the attached morphemes which their function is as suffixes. This study analyzes the morphophonemic process of Turkish verbs using the Word and Paradigm approach. The data of this study are the oral data of Turkish verbs got from the social media of YouTube. The data are collected by observing and noting. The morphophonemic process affected by the change of the sound is later analyzed using the padan method and Word and Paradigm or WP approach from the data collection. Through the approach, the word-formation rules are made for later, the effectiveness of the Word and Paradigm approach is studied in the morphophonemic analysis of Turkish verbs. The results show that there are different kinds of word-formation, and the WP approach effectively analyses Turkish verbs.